1955
DOI: 10.1021/j150527a012
|View full text |Cite
|
Sign up to set email alerts
|

The Ionization Potential and the Polarizability of Molecules

Abstract: Partial molal energy of mixing, kcal./mole (caled, by eq. 18a).functions for the pure hydrocarbons were not measured by Simons, et al., but were taken from other sources in the literature. In view of the agreement shown for the hydrocarbons in Fig. 1, it is probable that the vapor pressures used for the hydrocarbons are accurate while those measured for the fluorocarbons are not. ConclusionsThe heats of mixing paraffin hydrocarbons with fluorocarbons of the same carbon atom skeleton in liquid solution may be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Further evidence in support of the IET based polarizability analysis (for O 2 and CO) come from the work of Reed [48] and Bogaard et al [49] The molecular polarizability for O is given by 1.75 10 À40 Cm 2 V À1 [we converted the unit from cm 3 (Gaussian) to SI]. [48] The molecular polarizability [49] for CO is 2.031 10 À40 Cm 2 V…”
mentioning
confidence: 72%
“…Further evidence in support of the IET based polarizability analysis (for O 2 and CO) come from the work of Reed [48] and Bogaard et al [49] The molecular polarizability for O is given by 1.75 10 À40 Cm 2 V À1 [we converted the unit from cm 3 (Gaussian) to SI]. [48] The molecular polarizability [49] for CO is 2.031 10 À40 Cm 2 V…”
mentioning
confidence: 72%
“…When the electron energy exceeds the ionization potential, dissociative ionization will produce various fragments and species. Although tetrafluoromethane possesses a relatively high ionization potential (17.8 eV), it was selected as a process gas due to its fluorine/carbon (F/C) ratio, which corresponds with the ability to produce an overabundance of excited fluorine species in the plasma state (Kiser and Hobrock 1965;Reed 1955). Surfeit fluorine radicals can bind onto the surface of saturated and unsaturated hydrocarbons through hydrogen abstraction and double bond addition pathways, respectively (Fig.…”
Section: Tetrafluoromethane Plasma Treatment Of Polyethersulfone and mentioning
confidence: 99%
“…Notionally, averaged molecular polarisabilities are obtained as the sum of averaged bond polarisabilities of each of the bonds in the molecule [3], so that the total dispersion interaction will be a sum of such terms. For isotropic molecules, the expression reduces to equation (1). A simple combining rule would not be directly obtainable from the Hudson-McCoubrey method, since an extra equation would be required to solve for both components of the polarisability.…”
Section: Large Non-polar Moleculesmentioning
confidence: 99%
“…Over fifty years ago Reed [1] showed that the usual form for the combining rule for intermolecular attractive forces in unlike binary interactions, known as the Berthelot, or geometric-mean rule (given as equation (9) in this paper), is improved by the inclusion of ionisation potentials and molecular size. This results from consideration of the London theory of dispersion interactions [2], which is frequently described (e.g.…”
Section: Introductionmentioning
confidence: 96%